PUBLIC FINANCE AND WAR IN ANCIENT GREECE*. (25th March 2015) - Unknown
Abstract : Before the Persian Wars the Greeks did not rely on public finance to fight each other. Their hoplites armed and fed themselves. But in the confrontation with Persia this private funding of war proved to be inadequate. The liberation of the Greek states beyond the Balkans required the destruction of Persia's sea power. In 478bc Athens agreed to lead an alliance to do just this. It already had Greece's largest fleet. But each campaign of this ongoing war would need tens of thousands of sailors and would go on for months. No single Greek city-state could pay for such campaigns. The alliance thus agreed to adopt the Persian method for funding war: its members would pay a fixed amount of tribute annually. This enabled Athens to force Persia out of the Dardanelles and Ionia. But the Athenians also realized that their military power depended on tribute, and so they tightened their control of its payers. In so doing they turned the alliance into an empire.